Fountain, Barbados. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This is an image of what is called the Dolphin Fountain or Fountain Garden in Trafalgar Square, Bridgetown, Barbados. The Fountain commemorates the introduction of piped water to Bridgetown in 1861. In the background is the Parliament Building. This building is of historical architectural interest. Handwritten note on front of the card reads : We have just invested in some old custer?? ware. Mar. 24 – 1905 A. P. H. Also on the front :J.R.H. Siefert & Co. Ltd, Barbados. This is an undivided back postcard. Back of the postcard: AL HNT £3 (Handwritten in Pencil) Attached is a One Penny Barbados stamp ; BARBADOS MAR 24 ‘05 NEW YORK APR 1905; PAID E ALL Postcard addressed to: Miss Belle Clokey, 446 Nr. Milliace Street, Decatur, Dellwood, U.S.A.
Landscape; Color; 3 ½” x 5½ ”
Keywords: Fountains; Architecture; Historic sites; Monuments and memorials; Gardens; Historic buildings; Architectural elements; Cities and towns; Water; Parliament Buildings; Fountain Garden; Dolphin Fountain; Water fountains